1998
DOI: 10.1038/sj.onc.1201708
|View full text |Cite
|
Sign up to set email alerts
|

The kinase activity of c-Abl but not v-Abl is potentiated by direct interaction with RFXI, a protein that binds the enhancers of several viruses and cell-cycle regulated genes

Abstract: c-Abl, the non-receptor tyrosine kinase is associated with EP, a DNA element found in promoters/enhancers of di erent viruses and cell-cycle regulated genes. EP-DNA binds RFXI, a member of a novel family of DNA-binding proteins that is conserved through evolution and in yeast, it controls di erentiation and exit from the mitotic cycle to G 0 . EP-associated proteins are preferentially tyrosine phosphorylated and the associated c-Abl has strong tyrosine kinase activity. Here we investigated the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In contrast, the activation of nuclear c-Abl in S phase is through the detachment of the inhibitor Rb protein (3), whereas Abl may be activated by free radicals through dissociation of Pag/Msp23, an antioxidant protein that also inhibits Abl (7). Abl kinase activity can also be stimulated by the binding of several activator proteins, including the transcription factors c-Jun (8) and RFX1 (9), and the adapter protein Nck (10). These observations suggest complex regulation of c-Abl at multiple levels through binding or dissociation of activators and inhibitors and via direct phosphorylation.…”
Section: C-abl Has High Intrinsic Tyrosine Kinase Activity That Is Stmentioning
confidence: 99%
“…In contrast, the activation of nuclear c-Abl in S phase is through the detachment of the inhibitor Rb protein (3), whereas Abl may be activated by free radicals through dissociation of Pag/Msp23, an antioxidant protein that also inhibits Abl (7). Abl kinase activity can also be stimulated by the binding of several activator proteins, including the transcription factors c-Jun (8) and RFX1 (9), and the adapter protein Nck (10). These observations suggest complex regulation of c-Abl at multiple levels through binding or dissociation of activators and inhibitors and via direct phosphorylation.…”
Section: C-abl Has High Intrinsic Tyrosine Kinase Activity That Is Stmentioning
confidence: 99%
“…Furthermore, other SH3 binding proteins, such as Abi 1 and 2, are phosphorylated by c-Abl 7,8 and are therefore unlikely to inhibit it. Also, the adaptor protein Crk 26 and the DNA-binding protein RFX1 13 support and even potentiate c-Abl kinase activity in vitro. These findings lend support to the possibility that the cAbl kinase domain is under repression by an intramolecular mechanism.…”
Section: C-abl Kinase Activationmentioning
confidence: 99%
“…64 RFX1 interacts with the c-Abl SH3 domain and stimulates c-Abl kinase activity. 13 A limited number of RFX1 target genes have so far been identified, and the products of most of them are involved in DNA replication and repair. These include c-MYC, PCNA and the DNA-repair gene XRCC1.…”
Section: C-abl and G1 Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…p53, Rb, 3BP-1/3BP-2, AAP1, ATM and DNA-PK, PAG) (18). Some of the interacting proteins, such as PAG and Rb, were found to negatively regulate c-Abl kinase activity and function, whereas others, such as RFXI, an EP-DNA-binding protein that potentiates the kinase activity when bound to c-Abl, were found to be positive regulators for c-Abl (19).In this study we identified a novel c-Abl-interacting protein, * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
mentioning
confidence: 99%